Accuracy of Demirjian's four methods of dental age estimation in a sample of Saudi Arabian population. Issue 2 (4th March 2022) - Yassin, Syed M.
ABSTRACT: The study aimed to determine the accuracy of Demirjian's original, revised, four teeth and alternate four teeth methods for age estimation in a sample of the Saudi population. This cross-sectional study involved retrospective evaluation of orthopantomographs of 627 healthy children (407 males, 220 females) aged five to twelve years. Dental age (DA) was estimated using Demirjian's all four methods, and the accuracy was evaluated using the difference between chronological age (CA) and DA. Statistically significant differences between CA and DA were found in all the tested methods (p < 0.05). In males, Demirjian's four teeth approach was most accurate(0.30 ± 1.44 years), followed by the revised system(0.35 ± 1.46 years), alternate four teeth technique (0.37 ± 1.49 years), and the original method(0.44 ± 1.47 years).In females, the revised system was most accurate(0.39 ± 1.15 years), followed by the original method(0.56 ± 1.19 years), four teeth approach(0.60 ± 1.21 years), and alternate four teeth technique(0.63 ± 1.17 years).In the total sample, the revised system was most accurate(0.36 ± 1.36 years), while the original method was least accurate(0.48 years ± 1.38 years). According to the results, Demirjian's four teeth approach is recommended for estimating age in Saudi males and the revised method for Saudi females.